1980
DOI: 10.1111/j.1471-4159.1980.tb06600.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Requirement for Long‐lived Morphine‐dependent Activations of Adenylate Cyclase of Neuroblastoma × Glioma Hybrid Cells

Abstract: Morphine or norepinephrine at 10 p~ inhibit adenylate cyclase of NG108-15 neuroblastoma x glioma hybrid cells and gradually, over a period of 12 h or more, elicit a compensatory, persistent increase in adenylate cyclase activity. The cells are then dependent upon the receptor ligand for maintenance of normal cyclic AMP levels. Serum lipids or linoleic acid are required for the full expression of the long-lived morphine-dependent increase in adenylate cyclase activity, but serum lipids are not required for inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The failure of hydrolysis of the p-fatty acid from phospholipid by phospholipase A, to alter the acute opiate effect was in agreement with a previous report in which NG108-15 cells were cultured in a delipidized serum medium (Wilkening and Nirenberg, 1980). In those studies, although the chronic opiate effect was modified by culturing hybrid cells in delipidized serum, which altered the 0-fatty acid composition, acute opiate inhibition of adenylate cyclase was not altered.…”
Section: / P O -Osupporting
confidence: 92%
“…The failure of hydrolysis of the p-fatty acid from phospholipid by phospholipase A, to alter the acute opiate effect was in agreement with a previous report in which NG108-15 cells were cultured in a delipidized serum medium (Wilkening and Nirenberg, 1980). In those studies, although the chronic opiate effect was modified by culturing hybrid cells in delipidized serum, which altered the 0-fatty acid composition, acute opiate inhibition of adenylate cyclase was not altered.…”
Section: / P O -Osupporting
confidence: 92%
“…Since dedifferentiation is a common denominator among conditions in which a conversion from a,-to /3-receptor mediated glycogenolysis occurs in the rat liver (1), a possible role of fatty acids in the altered receptor response is plausible. Unsaturated fatty acids have been also implicated in the regulation of other, receptor mediated processes: Wilkening and Nirenberg (20) have documented that linoleic acid, a precursor of arachidonic acid, is required for the full expression of the long-lived morphine-dependent increase in adenylate cyclase activity in a neuroblastoma-glioma hybrid cell line (20).…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier report, Wilkening and Nirenberg (1980) have suggested that the fatty acid side chains of lipids are essential for the cellular expression of the compensatory increase in adenylate cyclase activity after chronic opiate treatment. With culture of NG108-15 hybrid cells in medium supplemented with delipidized serum, the compensatory increase in adenylate cyclase activity was removed.…”
Section: Discussionmentioning
confidence: 99%
“…With hydrolysis of the phospholipids with phospholipase C but not with phospholipase AZ, opiate inhibition of adenylate cyclase activity was attenuated (Law et al, 19836). Furthermore, by culturing the hybrid cells in delipidized serum and supplementing the media with selective fatty acids, Wilkening and Nirenberg (1980) suggested a specific requirement of linoleic acid in the chronic opiate-induced compensatory increase in adenylate cyclase activity. These data implicated a role of membrane lipids in the chronic opiate response.…”
mentioning
confidence: 99%